2012
DOI: 10.2217/rme.12.106
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering Strategies in Spinal Arthrodesis: The Clinical Imperative and Challenges to Clinical Translation

Abstract: Skeletal disorders requiring the regeneration or de novo production of bone present considerable reconstructive challenges and are one of the main driving forces for the development of skeletal tissue engineering strategies. The skeletal or mesenchymal stem cell is a fundamental requirement for osteogenesis and plays a pivotal role in the design and application of these strategies. Research activity has focused on incorporating the biological role of the mesenchymal stem cell with the developing fields of mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 135 publications
0
12
0
Order By: Relevance
“…For a rapid cell proliferation, low immunogenicity and foreign genes easily transfected; they have become the extensive seed cells for tissue engineering. Till date, although some animal models of human diseases have been constructed with MSCs, such as spinal cord injury (Evans et al 2013), osteogenesis imperfecta (Norambuena et al 2012), and diabetes mellitus (Godfrey et al 2012), more valuable therapeutic researches and clinical treatment of MSCs should be carried out to reveal the characteristics of MSCs. It has been confirmed that MSCs can be isolated from the umbilical cord (UCMSCs) and those cells can differentiate into many cell types (Qiao et al 2008), such as osteoblast (Jaiswal et al 1997), hepatocyte (Aurich et al 2009), and neurocyte (Soleimani et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For a rapid cell proliferation, low immunogenicity and foreign genes easily transfected; they have become the extensive seed cells for tissue engineering. Till date, although some animal models of human diseases have been constructed with MSCs, such as spinal cord injury (Evans et al 2013), osteogenesis imperfecta (Norambuena et al 2012), and diabetes mellitus (Godfrey et al 2012), more valuable therapeutic researches and clinical treatment of MSCs should be carried out to reveal the characteristics of MSCs. It has been confirmed that MSCs can be isolated from the umbilical cord (UCMSCs) and those cells can differentiate into many cell types (Qiao et al 2008), such as osteoblast (Jaiswal et al 1997), hepatocyte (Aurich et al 2009), and neurocyte (Soleimani et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, posterior lumbar fusion (PLF) is a standardized surgical technique that requires firm fixation for mechanical stability, and uses the addition of a bone graft to enhance bone formation [ 1 ]. The intervention consists of two main steps: a firm fixation for mechanical stability, and the addition of a biological substance for bone formation enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the suitability of bone-grafting materials must be tested for PLF and bone tissue engineering before any clinical application. Bone grafts and bone substitutes, with or without the addition of BM cells, as well as BMPs have all been used for PLF in recent years [ 1 ]. The use and type of any instrumentation is another matter to be considered [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, pieces of autograft bone, containing patient's own MSCs and a bone scaffold, are placed inside the defect area; the remaining bone void is filled with a so called 'graft expander', normally a synthetic scaffold, and mechanically stabilized. Graft material can be additionally loaded with concentrated BM aspirate from the same patient in order to provide additional MSCs [8,15,16].…”
Section: Bone Repairmentioning
confidence: 99%